Hábitos ecológicos y la conservación del ambiente en familias de la comunidad de Santo Tomás, región Loreto. 2020 - Pacaya García, Dennis Orlando (2022)
The study was designated as: Ecological habits and environmental conservation in families of the community of Santo Tomás, Loreto region. 2020. The objectives were: To determine if there is a significant relationship between ecological habits and the conservation of the environment in families of the community of Santo Tomás in Loreto. The non-experimental, quantitative research design was used. The research work is descriptive-cross-sectional. Having a simple probabilistic sample of 200 people living in Santo Tomás. The results achieved were developed through descriptive statistics. From the results obtained, about the respondents: they are between the ranges 35 and 50 years (36%) and 51 to 65 years (36%), prevailing the male (51.58%) and female (48.5%), counting the same with some degree of instruction: secondary level (63.5%), primary (25.5%) and higher (11.0%). Regarding ecological habits, there are results measured with a Likert scale, a high level (78%) of these inhabitants and habits of a regular level are considered to be 22% of this population. On aspects of environmental conservation, the people in the study according to the Likert analysis present high values (56.5%) to regular (43.5%). It is concluded that there is no correlation between ecological habits and environmental conservation. Therefore, there are sufficient reasons to reject the alternative hypothesis and accept the research hypothesis.